Re-membering and surviving : African American fiction of the Vietnam War - Hanshaw, Shirley A. J. (Michigan State University Press, 2021)
"A critical study of the black experience in the Vietnam War and its aftermath, this text interrogates the meaning of heroism based on models from African and African American novels: Captain Blackman (1972), John A. Williams; Tragic Magic (1978), Wesley Brown; Coming Home (1984), George Davis; and De Mojo Blues (1985), A. R. Flowers"--